Adjunctive transcranial alternating current stimulation for patients with major depressive disorder: A systematic review and meta-analysis - Zheng, Wei; Cai, Dong-Bin; Nie, Sha; Chen, Jian-Hua; Huang, Xing-Bing; Goerigk, Stephan; Brunoni, Andre Russowsky; Zheng, Wei (Frontiers in Psychiatry, 2023)
Objective We performed a meta-analysis of randomized, double-blind, controlled trials (RCTs) to systematically investigate the therapeutic effects and tolerability of transcranial alternating current stimulation (tACS) for the treatment of patients with major depressive disorder (MDD). Methods Electronic search of PubMed, PsycINFO, EMBASE, Chinese National Knowledge Infrastructure, Wanfang database, and the Cochrane Library up to 1 April 2022. Double-blind RCTs examining the efficacy and safety of tACS for patients with MDD were included. The primary outcome was the improvement of depressive symptoms following a course of tACS treatment. Data were analyzed using Review Manager Version 5.3 (Cochrane IMS, Oxford, UK). Study quality was assessed using the Cochrane risk of bias and Jadad scale. Publication bias was assessed using a funnel plot and the Egger test. Results We identified 883 articles, of which 4 RCTs with 5 active treatment arms covering 224 participants with MDD on active tACS (n = 117) and sham tACS (n = 107) were eligible for inclusion. Meta-analysis of depressive symptoms at post-tACS found an advantage of active tACS over sham tACS (n = 212, standard mean difference (SMD) = −1.14, 95% confidence interval (CI): −2.23, −0.06; I2 = 90%, P = 0.04). The significant superiority of active tACS over sham tACS in improving depressive symptoms remained in a sensitivity analysis. Active tACS was significantly superior to sham tACS regarding depressive symptoms at the 4 week follow-up (SMD = −1.07, 95% CI: −2.05, −0.08; I2 = 88%, P = 0.03) and study-defined remission [risk ratio (RR) = 2.07, 95% CI: 1.36, 3.14, I2 = 9%, P = 0.0006]. The discontinuation rate due to any reason was similar between the two groups (P > 0.05). All included studies were rated as high quality (Jadad score ≥ 3), with funnel plots of primary outcome not suggestive of publication bias. Conclusion tACS appeared to be modestly effective and safe for improving depressive symptoms in patients with MDD, although further studies are warranted.